Genes controlling skeletal muscle glucose uptake and their regulation by endurance and resistance exercise. Issue 2 (23rd November 2021) - Verbrugge, Sander A. J.; Alhusen, Julia A.; Kempin, Shimon; Pillon, Nicolas J.; Rozman, Jan; Wackerhage, Henning; Kleinert, Maximilian
Abstract: Exercise improves the insulin sensitivity of glucose uptake in skeletal muscle. Due to that, exercise has become a cornerstone treatment for type 2 diabetes mellitus (T2DM). The mechanisms by which exercise improves skeletal muscle insulin sensitivity are, however, incompletely understood. We conducted a systematic review to identify all genes whose gain or loss of function alters skeletal muscle glucose uptake. We subsequently cross‐referenced these genes with recently generated data sets on exercise‐induced gene expression and signaling. Our search revealed 176 muscle glucose‐uptake genes, meaning that their genetic manipulation altered glucose uptake in skeletal muscle. Notably, exercise regulates the expression or phosphorylation of more than 50% of the glucose‐uptake genes or their protein products. This included many genes that previously have not been associated with exercise‐induced insulin sensitivity. Interestingly, endurance and resistance exercise triggered some common but mostly unique changes in expression and phosphorylation of glucose‐uptake genes or their protein products. Collectively, our work provides a resource of potentially new molecular effectors that play a role in the incompletely understood regulation of muscle insulin sensitivity by exercise.